PENGEMBANGAN VIDEO ANIMASI “BANG DASI” BERBASIS APLIKASI CAMTASIA PADA MATERI BANGUN DATAR KELAS V SEKOLAH DASAR - Hikmah, Vela Nur; Purnamasari, Iin (Universitas Pendidikan Indonesia, 2017)
The purpose of this study is to analyze the feasibility and practicality of an animated video media “Bang Dasi” Camtasia application-based. The experiment was conducted in SDN Sugihmanik 04, District Tanggungharjo, Grobogan. This research development (R D) used ADDIE design (Analysis, Design, Development, Implementation, and Evaluation), which involved five stages of research, those are the analysis phase, design phase, development phase, implementation phase and evaluation phase. Based on the analysis, the average score obtained from the value of the material and results validation of the media that is 95.1% categorized as very feasible. Meanwhile, the score from media expert is 93.33% and from material expert is 96.86%. Animated video media “Bang Dasi” Camtasia application-based has effectiveness in fostering student interest and getting students’ responses (90.5%). This research conclude that animated video media “Bang Dasi” Camtasia application-based is worth using as learning media. Keywords: development, media, video animation, camtasia, two-dimentional figure.